Bibliometric analysis: sport pedagogy and physical activity in adolescents - Mulyana, Humaira Azzahra Putri; Suherman, Adang; Jajat, Jajat; Ferdiana, Fendi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
Research in the field of Sport Pedagogy and Adolescent Physical Activity has experienced dynamic development. This study examines trends and advancements in sport pedagogy and adolescent physical activity through a bibliometric analysis approach. By analyzing a total of 714 articles from 2014 to 2024, the study aims to understand the evolution, focus, and contributions of research in this field. Through bibliometric analysis of data obtained from the Scopus database, we investigate scientific publications related to sport pedagogy and adolescent physical activity. The use of VOSviewer software facilitates the visualization of collaboration networks among researchers, institutions, and research topics, providing deeper insights into the structure and dynamics of this research domain. This bibliometric method offers insights into research trends over time, identifies key topics of interest, and highlights contributions from various leading institutions and researchers in the field. The study provides valuable insights for educators, researchers, and policymakers to refine and implement effective physical activity programs aimed at addressing adolescent inactivity and promoting lifelong physical activity. Additionally, this research includes a systematic literature review to map potential future research areas based on current trends, offering comprehensive guidance for upcoming research in this field.